Choroidal Volume Evaluation after Photodynamic Therapy Using New Optical Coherence Tomography Imaging Algorithm - Miki Sato-Akushichi; Shinji Ono; Gerd Klose; Youngseok Song (MDPI AG, 2021)
To evaluate choroidal volume and thickness changes after photodynamic therapy (PDT) for chronic central serous chorioretinopathy (CSC). Chronic CSC eyes with a history of PDT were selected. Average choroidal volume, average choroidal thickness, the maximum and minimum choroidal thickness of the macula irradiated area and peripheral non-irradiated areas before and after one and three months of treatment were examined. A total of 14 patients with chronic CSC and 9 controls without any eye pathology were enrolled. The mean choroidal volume in CSC before and, and after one and three months of treatment were 2.36 (standard deviation: 0.70), 1.90 (0.69), 1.86 (0.66) mm3 for the central area, 1.25 (0.38), 1.14 (0.35), 1.13 (0.34) mm3 for superior nasal area, 1.47 (0.41), 1.28 (0.43), 1.26 (0.43) mm3 for superior temporal area, 1.07 (0.49), 0.95 (0.38), 0.93 (0.35) mm3 for inferior nasal area, 1.17 (0.38), 1.04 (0.32), 1.03 (0.33) mm3 for inferior temporal area. This study revealed the choroidal volume changes in a short period after PDT and a decrease in unirradiated choroidal volume was also shown after the treatment. The algorithm provided on the ARI Network enables to evaluate the choroidal changes quantitatively and qualitatively.